Paying Attention to Women's Ageing Bodies in Recovery From Substance Use - Shaw, April; Reith, Gerda; Pickering, Lucy (Frontiers in Psychiatry, 2022)
Background: Health-related research on women who use drugs tends to focus on reproductive and sexual health and treatment. Missing from the picture is an exploration of mid-life and older women’s bodily experiences of transitioning from long-term substance use into recovery. While there are a growing number of studies that explore the intersection of drug use and ageing, the gaps in analysis lie in the intersections between drug use, recovery, ageing, gender, and the body. Methods: In-depth qualitative interviews were undertaken with 19 women in the UK who self-identified as ‘in recovery’ from illicit drug use. The interviews were transcribed verbatim and analysed using Braun and Clarke’s thematic analysis techniques. The study received ethical approval from the University of Glasgow. Results: Key findings from the interviews relate to the women’s personal sense of power in relation to current and future health status, the challenges they endured in terms of ageing in recovery and transitioning through the reproductive life cycle, and the somatic effects of trauma on women’s recovery. The findings demonstrate that health in recovery involves more than abstinence from drugs. Discussion: Moving from the body in active drug use to the body in recovery is not without its challenges for mid-life and older women. New sensations and feelings - physical and mental - must be re-interpreted in light of their ageing and drug-free bodies. This study reveals some of the substantive sex-based differences that older women in active drug use and recovery experience. This has important implications for healthcare and treatment for women in drug services and women with histories of drug use more generally